(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
ABSTRACT The purpose of this study was to find out the achievement of targets, adaptability, job satisfaction and employee responsibilities in the application of personnel management information systems at BKPSDM Gowa Regency. This study used descriptive quantitative with the type quantitative survey. The population used by all employees at BKPSDM Gowa Regency, the research sample amounted to 41 people, sampling using the Saturated Sampling technique. Then the data obtained were analyzed using descriptive statistical analysis techniques. The results showed that the effectiveness of the implementation of the personnel management information system at the BKPSDM in Gowa Regency was included in the very effective category. The first indicator of target achievement scored 87.80% in the very effective category, the second indicator of adaptability scored 85.85% in the very effective category, the third satisfaction indicator scored 90.70% in the very effective category and the foruth indicator of responsibility obtained a score of 87.80% in the very effective category. Keywords: Effectiveness, Personnel Management Information System